ANALISIS PEMETAAN KESUKAAN KONSUMEN (CONSUMERâS PREFERENCE MAPPING) TERHADAP ATRIBUT KERIPIK PISANG DI KALANGAN MAHASISWA FAKULTAS PERTANIAN UNIVERSITAS RIAU - Saputra, Dodi; Restuhadi, Fajar; Rossi, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this research was to evaluate know the position of the best banana chips products and attributes of various kinds of banana chips. This objective of this study wasÂ to determine the level of consumer preference to a product that was banana chips. At this time which was still the lack of efforts of producers in developing their products.Â This research were carried out experiments using seven producs (brand of banana chip), which consists of KP1: Wahana, KP2: Alfamart, KP3: Mekar Jaya, KP4: Sumber Hidup,Â KP5: Winda, KP6: Elsa Snack, and KP7: Yadi Bersaudara.Â Data were analyzed statistically by using a Preference Test Mapping with assistance XL STAT software version 2014. Test hedonic and descriptive test analyzed were using Principal Component Analysis(PCA). Agglomerative hierarchical clustering (AHC) was used to see all grades of banana chips. Based on the descriptive analysis using PCA and hedonic analysis using the AHC showed that banana chips KP7 and analysis of the main components of the descriptive (PCA) test were then analyzed by using the preference mapping technique, with the sensory attributes used in banana chips products are banana flavor, saltiness, sweet taste, burnt, savory, crunchy, yellow, brownish yellow, banana scent, vacancy rate, texture crispness. The most preferred product in the study were Winda banana chips, Elsa Snack, and Yadi Bersaudara most favored by panelists.Â Keywords:Banana chips, consumer preferences, PCA, AHC.